A música na formação crítico-discursiva do aluno de língua estrangeira: uma pesquisa crítica de intervenção - Ibrahim, Elizete Cardoso (2008)
The aim of this research is to verify how new meanings related to practice are built, based on the music activities developed in foreign language (FL) classes. This investigation includes the researcher, a teacher and a group of Junior students of a public high school in the city of Cotia. The research was carried out during the school year of 2006 and the material collected is composed of video recordings of four classes and audio recordings of three reflective sessions. The data analysis is grounded on the following aspects: (1) analysis of turn-taking and symmetry relations among the participants (Marcuschi, 2006); (2) analysis of thematic content (Bronckart, 1999); and (3) observation of how the participants place their enunciates (Bronckart, 1999). Two questions guided this study: (1) Which is the objective of the activities in the analyzed classes? ; (2) How the reflective sessions contributed to change the teacher attitude face music activities? This study is grounded on vygotskian concepts of learning and development, mediation and ZPD (Vygotsky, 1993, 1994), as well as on the conception of language developed by Bakhtin (1929, 1979) and on the reflexive actions suggested by Smyth (1992). The present study adopted, as the methodology, the interventional collaborative research (Magalhães, 1992), inserted in the critical-collaborative research frame, in a dialectical standpoint of the research context. From the discussion of the results, based on the theoretical frame, I verified that there are contradictions in the teacher s speech during the reflective sessions, such as the individual assessment of her own pedagogical practice. These contradictions are pointed out and discussed during the third reflective session of the present work. This research also indicates that the collaboration set during reflective sessions helped to construct a collective environment of knowledge which can potentially generate significant changes regarding the teacher and researcher stand